A greedy policy for fleet-level radar resource management - Zhao, J (2013)
A model for a phased-array radar in the context of a defensive Naval system has been developed using hierarchical finite state machines. This model is used to study resource management for a fleet of ships equipped with one radar unit each. This fleet is under attack from aerial enemy agents. A control algorithm formulated on this specific model is used to dynamically generate a greedy policy for radar operation. The defense system is evaluated in its capability to acquire and track those aerial threats, in two configurations -centralized and decentralized (independent). The performance is quantified on the basis of time taken to establish the threat trajectory, time to compute the policy and the number of threats the system fails to track. A comparison of performance in the two configurations is provided. ©2013 IEEE.